2015
DOI: 10.1093/ofid/ofv194
|View full text |Cite
|
Sign up to set email alerts
|

Human Immune Response Varies by the Degree of Relative Cryptococcal Antigen Shedding

Abstract: Capsule shedding in cerebrospinal fluid is associated with inflammatory and Th2-mediated immune responses in HIV-infected individuals with cryptococcal meningitis. These findings provide important insight into the interactions that occur between the host immune system and the infecting strain of Cryptococcus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…However, without this specific CD4 T-cell response before CM treatment, patients had a markedly dysregulated immune upregulation of MIP-1-a and MCP-1 post-ART, leading to over-inflammation and IRIS [22]. This finding agrees with that of another study showing increased MCP-1 and MIP-1-a CNS expression at baseline associated with IRIS post-treatment, leading to the hypothesis of CD8 T-cell and myeloid trafficking, in response to these chemokines, playing a major role in the overreactive immune response and excessive inflammation [13].…”
Section: Iris Biomarkerssupporting
confidence: 89%
See 1 more Smart Citation
“…However, without this specific CD4 T-cell response before CM treatment, patients had a markedly dysregulated immune upregulation of MIP-1-a and MCP-1 post-ART, leading to over-inflammation and IRIS [22]. This finding agrees with that of another study showing increased MCP-1 and MIP-1-a CNS expression at baseline associated with IRIS post-treatment, leading to the hypothesis of CD8 T-cell and myeloid trafficking, in response to these chemokines, playing a major role in the overreactive immune response and excessive inflammation [13].…”
Section: Iris Biomarkerssupporting
confidence: 89%
“…Phagocytic macrophages are a primary line of defence against cryptococci; however, they can survive and replicate within the phagolysosomes of alternatively activated macrophages [14], contributing to fungal persistence. Further, granulocyte colony-stimulating factor (G-CSF) and granulocyte macrophage colonystimulating factor (GM-CSF), related to macrophage functionality and M1 polarization, are decreased pre-therapy and correlated to less effective fungal clearance [11,13] through a lack of M1 macrophages engulfing and degrading cryptococci [2]. In murine models, it has been shown that the fungus capsule destabilizes the immune response, causing a Th2mediated response and leading to increased mortality [15].…”
Section: Pathophysiology and Manifestationmentioning
confidence: 99%
“…Previous studies showed that pathogen-specific characteristics, such as the genotype or the degree of antigen shedding, influence immune responses to C. neoformans and the clinical outcome of patients (5,(7)(8)(9). Multilocus sequence typing (MLST) of 7 genetic loci has previously been used to identify genetically similar strains (5)(6)(7)(8)(9)(10). For example, studies of clinical isolates in both Uganda and Brazil showed higher patient mortality associated with sequence type 93 (ST93) strains (5,10).…”
mentioning
confidence: 99%
“…Institutional Review Board approvals were obtained from each participating site. A total of 106 patients that had culture-positive CSF for Cryptococcus and from which isolates were sequenced for genotypic analyses (5, 8) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Cryptococcus clinical isolates were colony-purified from the cerebrospinal fluid (CSF) specimens from patients enrolled in the COAT trial and multi-locus sequence type (MSLT) was determined previously (5, 8). The strains used in this study are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%